2009
DOI: 10.1007/s12306-009-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Telegraph antegrade nailing in the treatment of humeral fractures with rotator interval split technique

Abstract: Twenty-four proximal humeral fractures were treated by surgical internal fixation with a locked antegrade intramedullary nail. The purpose of this paper was to assess the clinical outcomes of proximal epiphyseal and diaphyseal humeral fractures treated with an antegrade humeral nail implanted after an interval rotator split. We treated six proximal epiphyseal fractures and seven bifocal fractures of the epiphysis and shaft and eleven diaphyseal fractures. The mean follow-up was 23 months (range 12 to 34 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Three studies additionally reported on outcomes following IMN of fracture dislocations [ 18 20 ], and three studies additionally reported on outcomes following IMN of combined proximal humerus and shaft fractures [ 11 , 21 , 22 ]. Only two of these studies were included, as explicit outcomes data for acute proximal humerus fractures could be elicited [ 11 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three studies additionally reported on outcomes following IMN of fracture dislocations [ 18 20 ], and three studies additionally reported on outcomes following IMN of combined proximal humerus and shaft fractures [ 11 , 21 , 22 ]. Only two of these studies were included, as explicit outcomes data for acute proximal humerus fractures could be elicited [ 11 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…20,[24][25][26][27] Other complications, including malunion, nonunion, cuff dysfunction, and osteonecrosis, have been described after both percutaneous screw or pin fixation [23][24][25]28 and intramedullary nailing. 19,23,[29][30][31][32][33][34][35][36][37][38][39][40] Conventional buttress plate fixation, using either cloverleaf, buttress or simple semitubular plates, offered the possibility of more rigid fracture fixation, 2,41-51 but fracture displacement was still prevalent as a result of screw cutout in the osteoporotic humeral head. 23 The revolution in the use of locking plate technology has now extended to the proximal humerus and site-specific locking plates have largely superseded conventional plate fixation in the last 10 years.…”
Section: Introductionmentioning
confidence: 99%